Die Schule und ihre Problemkinder (A)Normalität im 19. und 20. Jahrhundert, eine historisch-systematische Analyse - Deluigi, Tamara (Verlag Julius Klinkhardt, 2021)
The book deals with the question of categorization and diagnostic processes in the school sys-tem and the therewith linked specification of normality and deviation. The problem is elabo-rated by a historical-systematic approach: On the basis of current discourses on (un-)desirable characteristics and behavior in school, the question of how these categories have developed in the Swiss educational landscape since the establishment of the public elementary school around 1830 until the beginning of the 20th century is analysed. Among others one guiding principle is, that ideas, concepts, their implementation as well as related measures and actor participation have developed upon the connected history, culture and related systems and that these can only be understood and reflected within this context.The problem is elaborated on the basis of various sources from the pedagogical environment in Switzerland in the 19th century. These can be assigned to the context of the professionali-sation and training of teachers from 1830 onwards. On the one hand, there are pedagogical teaching materials and textbooks from the teacher training seminars of the defined research period. On the other hand, there are profession-specific newspapers - such as the "Schweize-rische Lehrerzeitung" - in which discourses of the teaching staff as well as of other actors are explored in order to negotiate the ideas of normality and deviation. By means of the analysis of the source corpus, in conjunction with discourse-analytical approaches and actor-centered institutionalism, key components in relation to the diagnosis of deviant children at school as well as processes of category formation and application are can be illustrated and analysed. The findings are finally discussed and problematised in the context of educational theories.One of the findings is, that in the development and application of categories it becomes apparent that different categories and patterns of differentiation are applied over different thematic epochs. It is interesting to note that this does not involve a replacement of existing attributions, but rather an addition by new categories, and thus an accumulation of the same. The variety of possibilities for classifying the "abnormal" at school thus increases conti-nuously over time. This accumulation again is associated with new measures and institutional changes. The increasing involvement of various actors and the professionalisation processes taking place are main factors therein. For example, it can be seen that teachers - and thus also elementary schools - did not just rely on achievement-based categories or relevant behavioral patterns at school when deciding to exclude children. They also relied on moral concepts and notions of what was considered "ideal". Around 1900, the focus was increasingly on assessing socio-economic factors and the "bourgeois" status of family constellations. Among others, poverty, working mothers, "immoral" lifestyles, intellectual limitations or alcoholism served as explanations for schoolchildren's "deviant" behavior or their bad school marks.